North-South Trade-related Technology Diffusion and Productivity Growth : Are Small States Different? - Schiff, Maurice; Wang, Yanling (Taylor and Francis, 2013)
The economies of small developing states tend to be more fragile than those in large ones. This paper examines this issue in a dynamic context by focusing on the impact of education and North–South trade-related technology diffusion (NRD) on TFP growth in small and large states in the South. The main findings are: (i) TFP growth increases with NRD, education and the interaction between the two; (ii) the impact of NRD, education and their interaction on TFP growth in small states is over three times that for large countries; and (iii) the greater TFP growth loss in small states has two brain–drain related causes: a substantially greater sensitivity of TFP growth to the brain drain, and brain drain levels that are much higher in small than in large states.